Exploration of Contextual Factors Affecting the Effectiveness of E-Kescatin Application Utilization: A Qualitative Study in Pringsewu Regency - Indrasari, Nelly; Risneni, Risneni; Aliyanto, Warjidin; Nurlaila, Nurlaila; Berliana , Eva; Marlina, Marlina (Jurnal Kesehatan, 2025)
The E-Kescatin application was developed as an innovation in premarital health services to support stunting prevention efforts through a digital approach. However, the effectiveness of utilization of this application still shows variations between regions and is not optimal at the implementation level. This study aims to explore the contextual factors that influence the effectiveness of the E-Kescatin application utilization in Pringsewu District, Lampung Province. The research used a qualitative approach with an exploratory study design. Informants were selected purposively, consisting of midwives, brides-to-be, Health Office officers, and MCH program managers. Data collection was conducted through in-depth interviews and focus group discussions. Data analysis was done thematically with an interpretative approach. The results identified five main themes that influence the effectiveness of app utilization, namely: (1) accessibility of technology and digital infrastructure; (2) digital competence of health workers; (3) perceived benefits from the user side; (4) policy and regulatory support at the local level; and (5) cross-sector integration in the implementation of premarital services. It is concluded that the effectiveness of E-Kescatin application utilization is influenced by contextual factors that include technical, social, and institutional aspects. Therefore, improving the success of application implementation requires a collaborative and adaptive approach to local conditions. The findings of this study provide a significant contribution to strengthening digital transformation policies in the field of reproductive health.